Narratives or Sources? Active Learning and the Teaching of Ancient Jewish History and Texts - Satlow, Michael L. (Teaching theology and religion, 2012)
During my career, I have regularly taught a survey course on the history of Jews and Judaism in the Persian, Greek, and early Roman periods (ca. 520 BCE – 70 CE). Student performance in the course has long concerned and puzzled me. By the end of the course students demonstrated familiarity with the narratives and concepts we covered, but most did not really “think historically.” They had great difficulties using and applying the historical tools they learned to new situations and evidence. In 2006 and again in 2010 I overhauled the course not only to improve it, but also to figure out how my students learned history. Using a wiki exercise, I traced how students learned and then applied these insights the next time I taught the course. In this essay I report on what I learned.